La lex aquilia: la estructura del damnum iniuria datum y su evolución a través de la interpretatio prudentium y la actividad pretoria - Sánchez Hernández, Luis Carlos (2018)
The Lex Aquilia, a third-century approved plebiscite, is the origin of the modern tortious liability on those legal systems descending from the roman system. Therefore, its study constitutes a necessity, because it allows us solid understanding of the previsions of the current civil codes, both in Europe as in Latin America.This article analyses the content of the three chapters in the plebiscite and the possible procedural clauses that followed; then, we will examine the structural element of the damnun injuria datum, crime regulated by chapters first and third of this law, and the evolution that each of these elements has experienced through jurisprudential interpretation, as well. Also, we will discuss how the Praetor extended the scope of application of the Lex Aquila through praetor acts; and, finally, the author will present, synthetically, the state of aff airs on Justinian codification.